Coatable Li4SnS4 Solid Electrolytes Prepared from Aqueous Solutions for All‐Solid‐State Lithium‐Ion Batteries. Issue 12 (31st May 2017) - Choi, Young Eun; Park, Kern Ho; Kim, Dong Hyeon; Oh, Dae Yang; Kwak, Hi Ram; Lee, Young‐Gi; Jung, Yoon Seok
Abstract: Bulk‐type all‐solid‐state lithium‐ion batteries (ASLBs) for large‐scale energy‐storage applications have emerged as a promising alternative to conventional lithium‐ion batteries (LIBs) owing to their superior safety. However, the electrochemical performance of bulk‐type ASLBs is critically limited by the low ionic conductivity of solid electrolytes (SEs) and poor ionic contact between the active materials and SEs. Herein, highly conductive (0.14 mS cm −1 ) and dry‐air‐stable SEs (Li4 SnS4 ) are reported, which are prepared using a scalable aqueous‐solution process. An active material (LiCoO2 ) coated by solidified Li4 SnS4 from aqueous solutions results in a significant improvement in the electrochemical performance of ASLBs. Side‐effects of the exposure of LiCoO2 to aqueous solutions are minimized by using predissolved Li4 SnS4 solution. Abstract : Superionic conductor : Highly conductive (0.14 mS cm −1 ) and dry‐air‐stable Li4 SnS4 is obtained by a scalable aqueous‐solution process, which enables direct wetting of solid electrolytes onto active material (LiCoO2 ). Moreover, the basicity of aqueous Li4 SnS4 solution alleviates detrimental surface degradation of LiCoO2 upon contact with water.